2016
DOI: 10.1177/0269881116663120
|View full text |Cite
|
Sign up to set email alerts
|

The effects of MDMA on socio-emotional processing: Does MDMA differ from other stimulants?

Abstract: ±3,4-Methylenedioxymethamphetamine (MDMA) is a popular recreational drug that enhances sociability and feelings of closeness with others. These "prosocial" effects appear to motivate the recreational use of MDMA and may also form the basis of its potential as an adjunct to psychotherapy. However, the extent to which MDMA differs from prototypic stimulant drugs, such as dextroamphetamine, methamphetamine, and methylphenidate, in either its behavioral effects or mechanisms of action, is not fully known. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
98
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 118 publications
7
98
1
1
Order By: Relevance
“…Both the psychoactive (including the entactogenic and nootropic properties) and the adverse effects being here described are consistent with 4,4′‐DMAR being a phenethylamine or MDMAlike compound (Bershad, Miller, Baggott, & DeWit, ; Iversen et al, ; Miliano et al, ; Schifano et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…Both the psychoactive (including the entactogenic and nootropic properties) and the adverse effects being here described are consistent with 4,4′‐DMAR being a phenethylamine or MDMAlike compound (Bershad, Miller, Baggott, & DeWit, ; Iversen et al, ; Miliano et al, ; Schifano et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…Domes et al reported increased attention bias to positive stimuli but no effects on negative stimuli, whereas Kim et al (2014) reported reduced attention toward negative expressions with no effect on positive expressions. It has been been suggested that MDMA produces prosocial effects by altering oxytocinergic signaling (Thompson et al, 2007), and in line with the effects of oxytocin on attention bias, we hypothesized that if MDMA is modifying attention through an oxytocinergic mechanism, then MDMA, but not MA (Bershad et al, 2016a), would positively bias visual attention.…”
Section: Introductionmentioning
confidence: 88%
“…In humans the drug increases self-report ratings of sociability and friendliness (Bedi et al, 2010;Bedi et al, 2009;Harris et al, 2002), as well as feelings of "trust," "openness," and "closeness with others" . Notably, the effects of MDMA are distinct from the effects of other pharmacologically related psychostimulant drugs (Bershad et al, 2016a). To understand the psychological processes, and ultimately the neurobiological processes, that produce these distinctive social effects of MDMA, we and others have investigated the influence of the drug on standardized behavioral tasks believed to model aspects of social behavior (for reviews see Bershad et al, 2016a;Kamilar-Britt and Bedi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Users report that it enhances feelings of empathy and social closeness, and controlled studies indicate that it dampens both behavioral and neural reactivity to negative social stimuli such as social threat and rejection (Bedi et al 2009; Bershad et al 2016; Frye et al 2014; Hysek et al 2012; Kirkpatrick et al 2012; Wardle and de Wit 2014). Interestingly, the drug is used recreationally in high-intensity social settings that may be physiologically stressful (Curran 2000; Parrott 2001, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although the drug may be used to cope with the psychological stress of these settings, it has been suggested that MDMA may actually increase the physiological stress response in these contexts (Parrott 2009). Several studies have investigated the effects of MDMA on responses to threatening social stimuli under controlled laboratory conditions (for reviews, see Kamilar-Britt and Bedi 2015; Bershad et al 2016). These studies show that MDMA reduces reactivity to faces expressing negative emotions.…”
Section: Introductionmentioning
confidence: 99%